Widespread Renal Polycystosis Induced by Crizotinib. Issue 4 (July 2015) - Di Girolamo, Marco; Paris, Ida; Carbonetti, Francesco; Onesti, Elisa Concetta; Socciarelli, Fabio; Marchetti, Paolo
With the widespread availability of biological antitumor drugs, the current scene of chemotherapies is changing. New chemotherapy agents, such as crizotinib, an inhibitor of anaplastic lymphoma kinase (ALK) and ROS1, usually used in pretreated advanced ALK-positive non-small-cell lung carcinoma, are more often used, and a description of the onset of side effects with suggestions for their management could be of interest for physicians. We describe a case of diffuse and aggressive renal polycystosis induced by crizotinib, which regressed after therapy, which could be of interest considering its wide extension and disappearance after the end of treatment. We also suggest some considerations from the literature and from the case reported that could be helpful in the management of this condition, which is known to be caused by crizotinib treatment.